PENGARUH DUKUNGAN SUAMI DALAM PROSES PERSALINAN DENGAN NYERI PERSALINAN DI RSIA BUNDA ARIF PURWOKERTO - Anggraeni, Diana Septi; ., Sumarni; Agustina, Ely Eko (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
The process of labour is a process that is quite horrible, exhausting, and very heavy for maternal, mother would think that labor will be passed with pain that can not be detained, that the longer mother will make the stress and worry, the time of delivery is needed a companion to relieve pain is felt when a maternity to knew out influence of husband the Labour support with maternity pain in Bunda Arif child mother hospital of Purwokerto. This study was observational with cross sectional approach. The sample used is Quota Sampling. The population of this research is all in the normal maternal in Bunda Arif child mother hospital of Purwokerto many as 30. Instrument research used questionnaire with simple linear regression. The majority of support provided during labor husband score of 15, the majority mothers perceived level of pain at the time of labor score of 5, so the better of support provided will make decreases her labor pains, the equation y = -0,431x+10.468. The better of support provided by husband in labor, the lower pain felt by the mother when the birth process. Increase the role of husband as a labor companion by giving more time intensive when accompanying his wife. Keyword : Husband support, Pain of Â Labour, Mother maternity